Uptake of family planning methods and unplanned pregnancies among HIV-infected individuals: a cross-sectional survey among clients at HIV clinics in Uganda - Wanyenze, Rhoda K (The International AIDS Society, 2011)
BACKGROUND: Prevention of unplanned pregnancies among HIV-infected individuals is critical to the prevention of mother to child HIV transmission (PMTCT), but its potential has not been fully utilized by PMTCT programmes. The uptake of family planning methods among women in Uganda is low, with current use of family planning methods estimated at 24%, but available data has not been disaggregated by HIV status. The aim of this study was to assess the utilization of family planning and unintended pregnancies among HIV-infected people in Uganda. METHODS: We conducted exit interviews with 1100 HIV-infected individuals, including 441 men and 659 women, from 12 HIV clinics in three districts in Uganda to assess the uptake of family planning services, and unplanned pregnancies, among HIV-infected people. We conducted multivariate analysis for predictors of current use of family planning among women who were married or in consensual union and were not pregnant at the time of the interview. RESULTS: One-third (33%, 216) of the women reported being pregnant since their HIV diagnoses and 28% (123) of the men reported their partner being pregnant since their HIV diagnoses. Of these, 43% (105) said these pregnancies were not planned: 53% (80) among women compared with 26% (25) among men. Most respondents (58%; 640) reported that they were currently using family planning methods. Among women who were married or in consensual union and not pregnant, 80% (242) were currently using any family planning method and 68% were currently using modern family planning methods (excluding withdrawal, lactational amenorrhoea and rhythm). At multivariate analysis, women who did not discuss the number of children they wanted with their partners and those who did not disclose their HIV status to sexual partners were less likely to use modern family planning methods (adjusted OR 0.40, range 0.20-0.81, and 0.30, range 0.10-0.85, respectively). CONCLUSIONS: The uptake of family planning among HIV-infected individuals is fairly high. However, there are a large number of unplanned pregnancies. These findings highlight the need for strengthening of family planning services for HIV-infected people.